EXPERIMENTAL APPROACH TO STUDYING VIOLENCE IN THE ADOLESCENT - T.A., Serebryakova; E.M., Kochneva; I.A., Koneva; L.B., Morozova; I.S, Ipatova; .G., Kolarkova O; O.V., Suvorova; O.A., Kostina (International Journal of Psychosocial Rehabilitation, 2020)
The article reflects the results of an empirical study aimed at establishing a relationship between the anxiety of adolescents and the experience of violence experienced by them. Based on the research results of both foreign and domestic scientists, we conclude that the violence experienced in childhood has the most serious consequences for a person and his personal development. Childhood traumatic experience, violation of physical and emotional boundaries, as a result of violence experienced by the child, throughout the next life will negatively affect a person. Based on the targets of our work, the study of the anxiety of adolescents as a consequence of the violence they experienced, we considered the diagnostic complex we proposed to be structured according to 2 substantive blocks. 1 block of diagnostic methods we focused on the study of the level of anxiety of respondents and included the method of Ch.D. Spielberger in the adaptation of Yu.L. Khanina and the scale of personal anxiety A.M. Parishioners. As an additional method at this stage of the study, we used the method of scientific observation. 2, the diagnostic unit was oriented directly by us to the study of violent forms of behavior that our respondents experienced and included the method of diagnosing the child’s perceptions of violence “Unfinished sentences” E.N. Volkova, a profile for the identification of child abuse M.M. The ICAST-C questionnaire is also multiplied. The generalized analysis of the experimental data we obtained not only confirms the direct correlation of anxiety and violence experienced by a teenager, but also actualizes the question of developing a proharma for preventing violence in a teenage environment.